34.5k views
3 votes
I need help with this and explain how to do it please!!
6x - 4z

User Skryvets
by
5.1k points

1 Answer

4 votes

Answer:

Simplifying

(6x + -4z)(6x + 4z) = 0

Multiply (6x + -4z) * (6x + 4z)

(6x * (6x + 4z) + -4z * (6x + 4z)) = 0

((6x * 6x + 4z * 6x) + -4z * (6x + 4z)) = 0

Reorder the terms:

((24xz + 36x2) + -4z * (6x + 4z)) = 0

((24xz + 36x2) + -4z * (6x + 4z)) = 0

(24xz + 36x2 + (6x * -4z + 4z * -4z)) = 0

(24xz + 36x2 + (-24xz + -16z2)) = 0

Reorder the terms:

(24xz + -24xz + 36x2 + -16z2) = 0

Combine like terms: 24xz + -24xz = 0

(0 + 36x2 + -16z2) = 0

(36x2 + -16z2) = 0

Solving

36x2 + -16z2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '16z2' to each side of the equation.

36x2 + -16z2 + 16z2 = 0 + 16z2

Combine like terms: -16z2 + 16z2 = 0

36x2 + 0 = 0 + 16z2

36x2 = 0 + 16z2

Remove the zero:

36x2 = 16z2

Divide each side by '36'.

x2 = 0.4444444444z2

Simplifying

x2 = 0.4444444444z2

Take the square root of each side:

x = {-0.666666667z, 0.666666667z}

Explanation: You don't need to explain with words, by doing this work you explained how to simplify and how you can do it in many ways to get the exact answer.

User Khai Vu
by
5.5k points